Needs Analysis of Physics Learning at High School in Padang to Develop Performance Assessment Application by The Worksheet Based-Scientific Literacy - Alia Rizky; Renol Afrizon; Amali Putra; - Hidayati (Universitas Negeri Padang, 2020)
Education in the 21st century is developing very rapidly. It can be seen from the many uses of science and technology in all the aspects of life. The development of technology also has a big impact on education. Learning cannot be separated from the assessment process. Teachers must be innovative, creative, and able to develop and use learning media that are in line with the development of science and technology. The researchers are interested in making assessment application that can be used as a medium to assist teachers in the process of grading assignment given to students. This type of research was an analysis that conducted in the context of the needs to make a skills assessment application. This research was conducted at class X of high school in Padang. The instrument used in this research was a questionnaires sheet containing positive and negative responses distributed by using the google form. The quistionnaires given have been validated by experts. The data analysis technique used was the descriptive statistical analysis. The results showed that the implementation of skill learning is not optimal epsecially on the uses of technology for students' assessment and most students lack of motivation in learning. The assignment given by teachers were still not optimal because most of the task were not related to the daily life. Then, the teacher was not optimal in giving worksheets before doing the practice. Therefore, the researcher designs the application of performance skills assessment that is equipped with worksheets based-scientific literacy